Information sources in patents - Adams, Stephen R. (Guides to information sources (London, England), 2006)
The completely new edition of this well respected reference work is aimed at information specialists and librarians as well as anyone needing to know where and how patent information can be found. The author discusses patent information within the context of the current legal framework for patents both from a national and international perspective. It also includes a chapter on future developments and their likely effect on patent information. In order to make successful use of patent information sources, it is essential that the reader fully understands the three major patent systems. The aut.